2008
DOI: 10.1196/annals.1405.013
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Thymectomy with the da Vinci Robotic System for Myasthenia Gravis

Abstract: Complete thymectomy (Thx) is a crucial part of treatment for myasthenia gravis (MG) and thymoma. The discussion about the necessity of radical, complete Thx and reduced invasiveness has led to no less than 14 different surgical approaches for Thx. The latest development is robotic-assisted surgery. Though its impact on minimally invasive surgery is not yet clear, it seems to be most promising for surgery in remote, narrow anatomical regions like the mediastinum. One hundred six consecutive robotic-assisted thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 62 publications
(128 reference statements)
4
84
1
8
Order By: Relevance
“…23 Because the most common indications for thymectomies are MG and thymomas, surgeons must be assured that robotic-assisted thymectomies can yield the same clinical improvements as other types of thymectomies. Thus, many series have confirmed that robotic-assisted thymectomy is a plausible treatment option for patients with MG. [24][25][26][27][28][29][30] Hartwich et al 30 showed that robotic-assisted thymectomy can improve symptoms in children with MG. Collectively, 82% to 92% of patients had improved symptoms of MG following robotic-assisted thymectomy, and the complete remission rate was as high as 28.5%.…”
Section: Thymectomymentioning
confidence: 99%
“…23 Because the most common indications for thymectomies are MG and thymomas, surgeons must be assured that robotic-assisted thymectomies can yield the same clinical improvements as other types of thymectomies. Thus, many series have confirmed that robotic-assisted thymectomy is a plausible treatment option for patients with MG. [24][25][26][27][28][29][30] Hartwich et al 30 showed that robotic-assisted thymectomy can improve symptoms in children with MG. Collectively, 82% to 92% of patients had improved symptoms of MG following robotic-assisted thymectomy, and the complete remission rate was as high as 28.5%.…”
Section: Thymectomymentioning
confidence: 99%
“…Finally, another disadvantage is represented by the placement of the surgeon, operating at a non-sterile console away from the patient (12,31). Thus, the sterile surgeon near the robot should be able to perform alone an emergency conversion.…”
Section: Tips Tricks and Pitfallsmentioning
confidence: 99%
“…Rea and Ashton both described in 2003 the first series of patients undergoing robotic thymectomy for MG, using the latter a right-sided approach with completion of the operation through the left side, while the former used only a left-side approach (8,9). In the following years, different authors described their results with robotic thymectomy both for thymic tumors and in cases of nonthymomatous myasthenia gravis (10)(11)(12). Analysis of literature data shows that robotic approach in thymectomy is a feasible and safe operation.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, minimally invasive surgery of the thymus has been developed, including a variety of access incisions, methods of exposure, visualisation and equipment [33,34]. This includes transcervical, extended transcervical, video-assisted thoracoscopy and robotic approaches (right or left, right and left, right and cervical, left and cervical, subxiphoid and right and left, cervical and subxiphoid).…”
Section: Surgery Principlesmentioning
confidence: 99%